Digital transformation of grades-related technologies at Dr. Jose P. Rizal Senior High School (2020–2024): A case study on usability and impact - Casas, Paul Enrique C.; Barrameda, Maria Lalaine M.; Elarmo, Jessa Mae C.; Rodriguez, Danielle Jana Roe P.; Prestado, Jessa Mae D. (Indonesian Journal of Education and Pedagogy, 2025)
This participatory case study examines the digital transformation of grades-related enabling technologies at Dr. Jose P. Rizal Senior High School from 2020 to 2024. Grounded in principles of sociotechnical theory and the Technology Acceptance Model (TAM), the study defines enabling technologies as digital solutions that enhance educational processes. It traces the institution's transition from manual procedures to a macro-enabled MS Excel eTool, and finally to the centralized Students Enrollment and Records Management System (SERMS). Using a mixed-methods approach that integrated historical document analysis, stakeholder feedback, and usability assessments, the research documented a four-phase progression from individual initiatives to institution-wide adoption. Findings indicate that strategic leadership, stakeholder collaboration, and user-centered design were pivotal to successful integration. Usability evaluation, based on the System Usability Scale and qualitative feedback from 31 faculty members, showed a statistically significant improvement from "Marginal" for the eTool to "Good" for SERMS, confirming strong user acceptance and improved administrative efficiency. Key success factors included sustained leadership and structured training, while primary challenges involved connectivity and interface navigation. This study contributes to understanding technology adoption patterns within the Southeast Asian public school context, offering a replicable framework for similar educational institutions pursuing digital transformation.